Integrating geographic information systems into veterinary education within the one health framework: an interdisciplinary approach - Contreras, Antonio; Cuevas, Víctor; Rivera-Gomis, Jorge; Sánchez, Antonio; Acevedo, Pelayo; Vicente, Joaquin (Frontiers in Veterinary Science, 2025)
IntroductionGeographic Information Systems (GIS) have become essential tools in animal and public health, particularly within the One Health framework. Despite their relevance in health and environmental science programs, GIS training is not yet fully integrated into veterinary curricula. This gap limits the ability of veterinary students to effectively utilize spatial data in their future professional practice.MethodsTo address this educational shortfall, we implemented a teaching innovation project at the University of Murcia, aimed at incorporating GIS training into veterinary education. Using open-access tools, we designed a series of tutorials, manuals, and exercises with graduated levels of complexity. These resources were based on real and simulated epidemiological datasets and focused on topics relevant to animal and public health. The tools employed included online GIS platforms such as the European Rabies Bulletin (ERB), free desktop applications like Epi Map from Epi Info 7 and QGIS, as well as ArcGIS Online, including its story map functionalities.ResultsThe educational pathway developed introduces GIS through a stepwise progression: (1) use of the ERB to explore official rabies data in Europe since 1977; (2) application of fictional disease data in rabbits using Epi Map and QGIS for beginners; and (3) analysis of official bovine tuberculosis sanitation campaigns in Ciudad Real (2007–2011) for more advanced users. The exercises support data visualization, geospatial analysis, and the generation of online outputs. They were designed to be accessible to users with no prior GIS experience and can be implemented remotely and asynchronously.DiscussionThis approach offers a scalable and accessible model for integrating GIS into veterinary education. The ability to visualize epidemiological patterns and combine health and production data with environmental risk layers fosters student engagement and spatial reasoning. Moreover, the capacity to publish results online enhances dissemination and interdisciplinary collaboration. Future work will focus on evaluating student learning outcomes and refining the pedagogical design based on user feedback.